Premature MicroRNA-1 Expression Causes Hypoplasia of the Cardiac Ventricular Conduction System - Samal, Eva; Evangelista, Melissa; Galang, Giselle; Srivastava, Deepak; Zhao, Yong; Vedantham, Vasanth (Frontiers in Physiology, 2019)
Mammalian cardiac Purkinje fibers (PFs) are specified from ventricular trabecular myocardium during mid-gestation and undergo limited proliferation before assuming their final form. MicroRNA-1 (miR-1), a negative regulator of proliferation, is normally expressed in the heart at low levels during the period of PF specification and outgrowth, but expression rises steeply after birth, when myocardial proliferation slows and post-natal cardiac maturation and growth commence. Here, we test whether premature up-regulation and overexpression of miR-1 during the period of PF morphogenesis influences PF development and function. Using a mouse model in which miR-1 is expressed under the control of the Myh6 promoter, we demonstrate that premature miR-1 expression leads to PF hypoplasia that persists into adulthood, and miR-1 TG mice exhibit delayed conduction through the ventricular myocardium beginning at neonatal stages. In addition, miR-1 transgenic embryos showed reduced proliferation within the trabecular myocardium and embryonic ventricular conduction system, a source of progenitor cells for the PF. This repression of proliferation may be mediated by direct translational inhibition by miR-1 of the cyclin dependent kinase Cdk6, a key regulator of embryonic myocardial proliferation. Our results suggest that altering the timing of miR-1 expression can regulate PF development, findings which have implications for our understanding of conduction system development and disease in humans.